The large family of PC4-like domains – similar folds and functions throughout all kingdoms of life. Issue 9 (1st September 2020) - Janowski, Robert; Niessing, Dierk
ABSTRACT: RNA- and DNA-binding domains are essential building blocks for specific regulation of gene expression. While a number of canonical nucleic acid binding domains share sequence and structural conservation, others are less obviously linked by evolutionary traits. In this review, we describe a protein fold of about 150 aa in length, bearing a conserved β-β-β-β-α-linker-β-β-β-β-α topology and similar nucleic acid binding properties but no apparent sequence conservation. The same overall fold can also be achieved by dimerization of two proteins, each bearing a β-β-β-β-α topology. These proteins include but are not limited to the transcription factors PC4 and P24 from humans and plants, respectively, the human RNA-transport factor Pur-α (also termed PURA), as well as the ssDNA-binding SP_0782 protein from Streptococcus pneumonia and the bacteriophage coat proteins PP7 and MS2. Besides their common overall topology, these proteins share common nucleic acids binding surfaces and thus functional similarity. We conclude that these PC4-like domains include proteins from all kingdoms of life and are much more abundant than previously known.